Męskość, kobiecość, androgynia a relacje między życiem osobistym i zawodowym = Masculinity, femininity, androgyny and relationships between work and family life - Lipińska-Grobelny, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the research presented in this article is to examine whether biological sex and psychological gender distinguish the relationship between work and home. The mentioned relationships will be analyzed both from the negative perspective (conflict and negative spillover between roles), as well as from the positive perspective (positive spillover between roles). The study involved 436 people (218 women and 218 men).
Keywords: męskość; kobiecość; androgynia; masculinity; femininity; androgyny; W-F/F-Wconflict and negative spillover; W-F/F-W positive spillover